Usia Berhubungan Dengan Preeklampsi Pada Ibu Hamil di Puskesmas Cipamokolan Bandung - Jayanti, Tri Nur; Rustikayanti, R Nety; Tambunan, Irisanna (Care : Jurnal Ilmiah Ilmu Kesehatan, 2023)
Preeclampsia is a systemic disorder 20 weeks of gestation, characterized by a BP 140/90 mmHg and proteinuria. These abnormalities can affect both the mother and fetus. The cause of preeclampsia was still unknown. Several studies have reported different results regarding the risk factors associated with preeclampsia. Therefore, research about the factors that influence preeclampsia at the Cipamokolan Health Center needs to be carried out to determine further prevention programs. The case-control was used as the study design. The population is all pregnant women data in the Cipamokolan Health Center during the past year. The study sample was taken by purposive sampling based on the specified criteria. A total of eighteen respondents were recruited in the case group and 97 respondents in the control group. Data obtained secondary from medical records. The data were analyzed using the Chi-Square. The results showed a relationship between maternal age and preeclampsia (p-value = .036 .050), and there was no relationship between gravidity and pregnancy intervals with preeclampsia in pregnant women at the Cipamokolan Health Center. A pregnancy spacing program is recommended to avoid preeclampsia during pregnancy.